Persepsi Dosen Dan Tenaga Kependidikan Pada Kebijakan Merdeka Belajar-Kampus Merdeka (MBKM) - Levyda, Levyda; Astuti, Titin; Widiati, Euis (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The MBKM policy is designed to produce quality human resources. Although it has been socialized, not all lecturers and staff understand the implementation. To facilitate policy implementation, it is necessary to know the perceptions of lecturers and staff on the policy. This research is a case study and uses a mix method. To improve the understanding of lecturers and staff, offline and online socialization by Dikti and Universities needs to be improved. An effective Dikti socialization is through YouTube, while university socialization should be done offline and online. To increase the involvement of lecturers, in addition to the manual, training should be held, especially on the calculation/equalization of credits. Relationships with partners need to be improved and socialized to lecturers and staff. Changes in basic tasks need to be followed up with a review of the task load and rewards.